SELECTING OF YOUNG SWIMMERS BASED ON ANTHROPOMETRIC AND MORPHOFUNCTIONAL INDICATORS (Sciental Journal of Education Humanities and Social Sciences, 2025)
The article provides recommendations for predicting the sports results of young swimmers based on their morphofunctional indicators and for optimizing the training process. The primary focus is directed towards classifying the factors that determine the effectiveness of selection, developing a model for selection based on anthropometric indicators, studying the influence of swimmers' body length in relation to standard biological development on sports results, and creating criteria aimed at improving the efficiency of selection.